2022
DOI: 10.1038/s41408-022-00670-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating agent and venetoclax with FLT3 inhibitor “triplet” therapy in older/unfit patients with FLT3 mutated AML

Abstract: In older/unfit newly diagnosed patients with FLT3 mutated acute myeloid leukemia (AML), lower intensity chemotherapy (LIC) in combination with either a FLT3 inhibitor or with venetoclax results in poor overall survival (median 8 to 12.5 months). We performed a retrospective analysis of 87 newly diagnosed FLT3 mutated AML patients treated on triplet (LIC + FLT3 inhibitor + Venetoclax, [N = 27]) and doublet (LIC + FLT3 inhibitor, [N = 60]) regimens at our institution. Data were collected from prospective clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…87 A phase I/II study explored the triplet combination based on azacitidine, venetoclax and gilteritinib for FLT3-mutated AML patients with de novo (11 patients) or refractory/relapsing (15 patients) disease. 86 In ND AML patients, 82% of CRs were observed, with 18% of patients proceeding to HSCT; in R/R AML patients, 27% of CRs were observed. 88 New drug combinations involving VEN are under preclinical for the therapy of FLT3-mutated AMLs.…”
Section: Flt3-mutatedmentioning
confidence: 96%
See 1 more Smart Citation
“…87 A phase I/II study explored the triplet combination based on azacitidine, venetoclax and gilteritinib for FLT3-mutated AML patients with de novo (11 patients) or refractory/relapsing (15 patients) disease. 86 In ND AML patients, 82% of CRs were observed, with 18% of patients proceeding to HSCT; in R/R AML patients, 27% of CRs were observed. 88 New drug combinations involving VEN are under preclinical for the therapy of FLT3-mutated AMLs.…”
Section: Flt3-mutatedmentioning
confidence: 96%
“…After a median follow-up of 24 months, patients receiving the triplet regimen displayed a longer mOS than those treated with the doublet regimen: not reached vs. 9.5 months, respectively. 86 Another recent study explored the triplet drug combination based on quizartinib (a second-generation FLT3 inhibitor), VEN and DEC in newly diagnosed and R/R patients with FLT3-ITD mutated AML. 87 Preclinical studies supported the rationale of the association of VEN with quizartinib.…”
Section: Flt3-mutatedmentioning
confidence: 99%
“…The median 2-year OS for newly diagnosed and relapsed or refractory AML patients, when treated with triple therapy, was 80% and 29%, respectively [ 134 ]. In addition, in a retrospective analysis in FLT3-mutated patients, CR/CRi rates improved to 93% with triple therapy (low intensity chemotherapy, FLT3 inhibitor and venetoclax) compared to 70% with double therapy (low intensity chemotherapy and an FLT3 inhibitor) [ 135 ]. Possibly, future treatment options for FLT3-mutated AML patients should include the combination of venetoclax together with an FLT3 inhibitor.…”
Section: Prediction Of Active Venetoclax-based Combination Therapies ...mentioning
confidence: 99%
“…The composite complete remission (CRc) rates in patients with newly diagnosed AML achieve 92% and 62% in R/R patients ( 64 ). Moreover, a retrospective analysis of their team demonstrated that older and unfit adult patients with newly diagnosed FLT3 mutated AML receiving a triplet regimen (lower intensity chemotherapy + FLT3 inhibitor + venetoclax) had a significantly higher CR/CRi rate (93% vs. 70%, P = 0.02) and longer median overall survival (NR vs. 9.5 months, P < 0.01) compared with doublet (lower intensity chemotherapy + FLT3 inhibitor) regimens ( 65 ). Overall, the combination of venetoclax and FLT3 inhibitors may be an effective frontline regimen for FLT3 mutated AML, which should be further validated prospectively.…”
Section: Flt3 Inhibitors For Aml Therapymentioning
confidence: 99%